The Insides of Outdoor Recreation Users towards Recreation Resource Impacts at Taman Negara Pahang, Kuala Tahan. Issue 1 (1st April 2022) - Bookhari, S N; Hashim, Z; Khalid, M Md.; Jamaludin, M A
Abstract: One of the most popular activities in the natural environment is trail walking and hiking. In such necessity, the trail is considered key to the recreational amenity available for the outdoor recreation users with safe accessibility to appreciate the natural and scenic environment. Taman Negara Pahang is the largest park in Malaysia and is located at one of the oldest rainforests in the world. The park has excellent advantages in attracting outdoor recreation users but facing a substantial impact on its recreation resources. The impacts cause undesirable change and degrade the components of recreation resources such as soil, vegetation, wildlife and water resources. This issue threatens its integrity to maintain the benefits of recreation function and reduce the quality of the visitor experience due to the ecological impacts. Thus, it is crucial to assess the extent to which outdoor recreation users perceived recreation resource impacts in Taman Negara Pahang. This research has two objectives: 1) to identify the outdoor recreation users' perceptions toward recreation resource impacts, and 2) to analyse the outdoor recreation users' level of acceptance toward recreation resource impacts. There are four entrances, i.e. Kuala Tahan and Sungai Relau in Pahang, Kuala Koh in Kelantan dan Tanjung Mentong in Terengganu. This research chooses explicitly Kuala Tahan because it is the main gateway to the park with the most facilities and amenities for the users. The primary research method is a questionnaire survey on outdoor recreation users after completing their activity. They will be intercepted at Bukit Teresek Trail, Canopy Walkway Trail and Lubok Simpon Trail. The survey was conducted from the 4th until the 9th of September, with 60 respondents involved. The expected outcome of this research is to provide a baseline understanding of the designated trail and effectively facilitate targeted experiential opportunities of a respected environment.